2018
DOI: 10.1016/j.appet.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of multiple energy balance related behaviors is associated with body fat composition indicators in adolescents: Results from the HELENA and ELANA studies

Abstract: The objective of this study was to identify clustering patterns of four energy balance-related behaviors (EBRB): television (TV) watching, moderate and vigorous physical activity (MVPA), consumption of fruits and vegetables (F&V), and consumption of sugar-sweetened beverages (SSB), among European and Brazilian adolescents. EBRB associations with different body fat composition indicators were then evaluated. Participants included adolescents from eight European countries in the HELENA (Healthy Lifestyle in Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(78 citation statements)
references
References 46 publications
2
61
0
3
Order By: Relevance
“…Children and adolescents who reported more than 2 h of sedentary behavior were over-represented in the high drinkers with SSB cluster; those who reported being physically active once a week to twice a month were under-represented. A recent cluster analysis of data from the ELANA and HELENA studies in children and adolescents reported clusters characterized by sedentary behavior and SSB consumption [72]. This is not surprising given the established links between sedentary behavior and less healthy dietary intake including SSB consumption [71, 73, 74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children and adolescents who reported more than 2 h of sedentary behavior were over-represented in the high drinkers with SSB cluster; those who reported being physically active once a week to twice a month were under-represented. A recent cluster analysis of data from the ELANA and HELENA studies in children and adolescents reported clusters characterized by sedentary behavior and SSB consumption [72]. This is not surprising given the established links between sedentary behavior and less healthy dietary intake including SSB consumption [71, 73, 74].…”
Section: Discussionmentioning
confidence: 99%
“…Those who reported sedentary behavior greater than 2 h a week and/or being physically active once a week to twice a month were over-represented in the very high drinkers–water cluster . While this may appear contradictory, this phenomenon has been reported before and is probably due to those who report being sedentary for two or more hours per day compensating by being physically active at other times of the day [72]. Clearly, the prevention and treatment of overweight and obesity in children and adolescents requires a multifaceted approach, which focuses on changing dietary habits, including reducing SSB consumption, and reducing sedentary behavior and or increasing physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…A magatartás szintjén elkülönült az egészségtudatos, a nem egészségtudatos magatartás, valamint egy kifejezetten a nyersétel-alapú étrendet preferáló táplálkozás, amely a legkisebb arányban volt jelen a mintában. Bár a legnagyobb arányban a fiatalok egészségtudatos magatartást követtek, jelen van az ellenkezője is, ami megfelel a szakirodalomban fellelhető adatoknak [5,10,11]. Ez azt a kettősséget jelzi, hogy a fiatalok -bár egyre egészségtudatosabbak a táplálkozás terénaz egészségkockázatos ételekről sem mondanak le.…”
Section: Eredeti Közleményunclassified
“…Ez az életszakasz e szempontból igen kritikus, hiszen a gyermekkori táplálkozási szocializáció az egyre inkább autonómmá váló döntésekkel jelentősen módosulhat (sajnos, mint a kutatások igazolják, nem kedvező irányba, például gyorsételek, energiaitalok stb.) [7,10,11]. A prevenciós programok a leggyakrabban a szerfogyasztási formákra fókuszálnak, pedig az egészségtudatos táplálkozás kialakítása szintén fontos prioritást kell, hogy képezzen.…”
Section: Eredeti Közleményunclassified
See 1 more Smart Citation